A Panicum‐derived chromosomal segment captured by Hordeum a few million years ago preserves a set of stress‐related genes. (15th March 2021) - Mahelka, Václav; Krak, Karol; Fehrer, Judith; Caklová, Petra; Nagy Nejedlá, Michaela; Čegan, Radim; Kopecký, David; Šafář, Jan
Summary: Intra‐specific variability is a cornerstone of evolutionary success of species. Acquiring genetic material from distant sources is an important adaptive mechanism in bacteria, but it can also play a role in eukaryotes. In this paper, we investigate the nature and evolution of a chromosomal segment of panicoid (Poaceae, Panicoideae) origin occurring in the nuclear genomes of species of the barley genus Hordeum (Pooideae). The segment, spanning over 440 kb in the Asian Hordeum bogdanii and 219 kb in the South American Hordeum pubiflorum, resides on a pair of nucleolar organizer region (NOR)‐bearing chromosomes. Conserved synteny and micro‐collinearity of the segment in both species indicate a common origin of the segment, which was acquired before the split of the respective barley lineages 5–1.7 million years ago. A major part of the foreign DNA consists of several approximately 68 kb long repeated blocks containing five stress‐related protein‐coding genes and transposable elements (TEs). Whereas outside these repeats, the locus was invaded by multiple TEs from the host genome, the repeated blocks are rather intact and appear to be preserved. The protein‐coding genes remained partly functional, as indicated by conserved reading frames, a low amount of non‐synonymous mutations, and expression of mRNA. A screen across Hordeum species targeting the panicoid protein‐coding genes revealed the presence of the genes in all species of the section Stenostachys . In summary, our study shows that grass genomes can contain large genomic segments obtained from distantly related species. These segments usually remain undetected, but they may play an important role in the evolution and adaptation of species. Significance Statement: Studies on the dynamics and evolution of horizontally transferred genetic material within host genomes are lacking. We investigate the nature and evolution of a large DNA segment from a donor closely related to present‐day Panicum (Panicoideae) occurring in the nuclear genomes of species of the barley genus Hordeum (Pooideae). The conserved nature of the segment, comprising partly functional protein‐coding genes, suggests that the transfer from Panicum might have played a beneficial role in the evolution of the genus Hordeum .